Adaptive station-keeping strategy for wave gliders considering uncertain environmental disturbances. (1st June 2023) - Yu, Peiyuan; Sun, Xiujun; Zhou, Ying; Sang, Hongqiang; Zhang, Shuai
Abstract: The wave glider (WG) is a new type of marine mobile observation platform, which has the ability to conduct long-term and large-scale ocean observations. Due to the characteristics of low speed and weak maneuverability, it is difficult to have a good control effect on the wave glider, especially in the case of large environmental disturbance. An adaptive station-keeping strategy integrated with a modified weather optimal positioning control (MWOPC) and an adaptive dead circle control (ADCC) is put forward for wave gliders in this paper, which can adaptively adjust the radius of the dead circle to resist time-varying environmental disturbance. More specifically, focusing on dynamically balancing the actuator energy consumption and station-keeping accuracy, a simplified battery discharge level function is designed to adjust the ratio gain between the actuator energy consumption and distance error in the ADCC. A closed-loop control is put forward with a dynamic model of the "Black Pearl" wave glider and a station-keeping strategy is given. The simulation and sea trial results show that the proposed station-keeping strategy can achieve good station-keeping effect under different environmental disturbances and adaptively change the energy consumption based on the battery charge level. Highlights: A new station-keeping strategy with adaptive dead circle control was for WG with time-varying disturbance and uncontrolled velocity. An objective function including a simplified battery discharge level function is proposed to balance the positioning accuracy and energy consumption. Simulations and sea trials of a closed-loop motion control embedded with the dynamic of the wave glider were put forward.